PENERAPAN GAYA MENGAJAR INKLUSI DALAM UPAYA MENINGKATKAN HASIL BELAJAR DRIBBLING PERMAINAN SEPAK BOLA PADA SISWA KELAS XI SMK PARULIAN 1 JI. STADION TELADAN MEDAN TAHUN AJARAN 2017/2018 - Fascal Rio Chandra Sinaga (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2018)
The research will be carried out at SMK Parulian 1 Medan. JI address. Medan Exemplary Stadium. This research was carried out in the 2017/2018 academic year in July 2017. The subjects in this classroom action research were class XI SMK Parulian 1 Medan in the 2017/2018 academic year, amounting to 36 students with 20 male students and 16 female students. This research method is Classroom Action Research. Based on student learning outcomes, there was an increase in the process of dribbling learning outcomes in soccer games "through inclusive teaching style" in cycle I, after the first learning outcomes test it can be seen that students' initial ability to perform dribbling techniques in soccer games is still low. Of the 36 students who were the subjects in this study, it turned out that only 20 students (55,550/0) already had learning mastery, while the rest, namely 16 students (44,450/0) did not yet have learning mastery. The average value obtained only reached 69.91. Meanwhile, in the second cycle, it can be seen that the students' ability to perform classical learning outcomes tests has increased. It turned out that out of 36 students, there were 32 students who completed (88,880/0) who already had mastery learning, while the rest, namely 4 students (11,120/0) did not have mastery learning. The average value obtained only reached 77.08. Based on this, it can be concluded that learning using inclusive teaching styles can improve dribbling learning outcomes in playing football in class XI students of SMK Parulian 1 JI. Medan Model Stadium T.A. 2017/2018